2022
DOI: 10.3390/w14213402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fires on Microbial and Metazoan Communities in Peatlands

Abstract: The increase in the frequency of peatland fires is due to both global climate change and deliberate human activity. The primary aim of the study was to investigate the structure of microbial communities and nematodes before and after a peat bog fire, as well as to analyse the relationships between food web components. Hydrological and physicochemical parameters were analysed during the period before the fire (2018 and 2019) and after the fire (2020 and 2021—2, 4, 8, and 12 months after the fire). The fire clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…On the post-fire peatland pH measurement, [21,22] show two kinds of conditions of pH, it can be increasing and/or decreasing. Post-fire peatland pH measurements by [15,16,18,[23][24][25] showed that the pH condition was increasing. Meanwhile, post-fire measurements by [26][27][28] show the pH was decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…On the post-fire peatland pH measurement, [21,22] show two kinds of conditions of pH, it can be increasing and/or decreasing. Post-fire peatland pH measurements by [15,16,18,[23][24][25] showed that the pH condition was increasing. Meanwhile, post-fire measurements by [26][27][28] show the pH was decreasing.…”
Section: Introductionmentioning
confidence: 99%